Productive behavior of Nile tilapia (Oreochromis niloticus) including high levels of soybean meal in the diet - Llanes, J.; Toledo, J. (Cuban Journal of Agricultural Science, 2011)
A total of 270 fingerlings of Nile tilapia (Oreochromis niloticus) (12.82 + 0.03 g of initial mean weight) was distributed according to one-way model in three triplicate treatments, to evaluate the possibility of using high percentages of soybean meal in the feeding of tilapias during 60 d. The treatments consisted of a control diet with 50 % of soybean meal and two experimental diets, with 55 and 60 % of this meal. The results showed that the treatment with 55 % of soybean meal, compared with the control, did not show significant differences for final weight (63.3 and 66.4 g), feed conversion (1.8 and 1.7) and protein efficiency (1.9 and 2.0). However, with the contribution of 60 %, there was impairment in final weight (52.8 g), feed conversion (2.1) and protein efficiency (1.7). The survival was high in all the treatments (higher than 93 %), which evidenced that high levels of this protein source are not responsible for the mortality. It is concluded that it is feasible including up to 55 % of soybean meal in the feeds of Nile tilapia. Also, assessing this level for longer feeding times is suggested. Key words: feeding, tilapia, soybean.